Antimicrobial activity of cholanic acids’ stereoisomers compared to cholic acid on the test cultures of microorganisms - Barsuk, D; Stremouhov, O; Kovalenko, S (Annals of Mechnikov’s Institute, 2020)
The paper presents the results of a study of microbiological activity 3α and 3β amino bile acids. We revealed high antimicrobial activity. The availability and range of antimicrobial activity were revealed by the method of serial dilutions in a solid nutrient medium and shown as bacteriostatic as bactericidic effects.